The Impact of Chatgpt on English as a Foreign Language Learners’ Writing Skills-An Experimental Study at Georgian Universities - Pipia, Ekaterine; Gurgenishvili, Tamar (European Scientific Journal, ESJ, 2025)
This study explores the impact of ChatGPT on English as a Foreign Language (EFL) students’ writing skills. The integration of advanced AI tools like ChatGPT has transformed educational experiences, offering significant potential to enhance writing competence through personalized feedback and interactive writing practice. Conducted in a Georgian higher education context, the study involved 33 B2-level students divided into experimental and control groups over six weeks. The experimental group used ChatGPT for writing assistance, while the control group received traditional instruction. Results showed that ChatGPT significantly improved students’ writing performance, highlighting its efficacy as an educational tool. However, concerns about ethical use and over-reliance on AI were noted, emphasizing the need for a balanced integration of technology in language learning.